ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN KERJA SISWA SMK NEGERI 1 LANGGUDU KABUPATEN BIMA - Nurbaya; Husain Syam; Patang (UNM Journal of Technology and Vocational, 2022)
This study aims to determine: (1) Is there any influence of knowledge on the work readiness of students at SMK Negeri 1 Langgudu. (2) Is there any influence of learning motivation on the work readiness of students of SMK Negeri 1 Langgudu. (3) Is there any influence of attitude on the work readiness of students of SMK Negeri 1 Langgudu. (4) Is there any influence of skills on the job readiness of SMK Negeri 1 Langgudu students. (5) Is there any effect of knowledge, learning motivation, attitudes, skills simultaneously on the work readiness of students of SMK Negeri 1 Langgudu. The research analysis used in this study is descriptive analysis with Ex-post facto quantitative research through a correlational approach using a survey method with a population of all students of SMK Negeri 1 Langgudu, Bima Regency. The sample of this study consisted of 64 respondents from four fisheriesmajors. The sampling technique used in this study is Proportional Random Sampling. Data were collected using a questionnaire (questionnaire) which was distributed directly and google form to determine the variable X (knowledge, learning motivation, attitudes, skills) and variable Y (work readiness). Using Pearson Product Moment data analysis techniques. The results showed that: (1) Based on the results of the descriptive analysis, knowledge was categorized in the medium category by 80%. (2) Based on the results of the descriptive analysis of learning motivation is categorized in the medium category by 72%. (3) Based on the results of the descriptive analysis, attitudes are categorized in the medium category by 72%. (4) Based on the results of the descriptive analysis, skills are categorized in the medium category by 74%. (5) Based on the results of the descriptive analysis of student work readiness categorized in the medium category by 73%. Based on the results of the analysis of hypothesis testing that knowledge, learning motivation, attitudes, skills on job readiness are positive at 0.716. The influence of knowledge, learning motivation, attitudes, skills on job readiness is 51.3% while the rest is influenced by other variables that are not measured